2006
DOI: 10.1007/s00018-005-5412-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of phosphatidylinositol 3-kinase activity prevent cell cycle progression and induce apoptosis at the M/G1 transition in CHO cells

Abstract: Phosphatidylinositol 3-kinase (PI3-kinase) activity has been implicated in regulating cell cycle progression at distinct points in the cell cycle by preventing cell cycle arrest or apoptosis. In this study, the role of PI3-kinase activity during the entire G1 phase of the ongoing cell cycle was studied in Chinese hamster ovary (CHO) cells synchronized by mitotic shake-off. We show that inhibition of PI3-kinase activity during and 2 h after mitosis inhibited cell cycle progression into S phase. In the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…This notion was consistent with the conclusions in other neuronal cell death models, including mild cerebral ischemia [5], glutamate toxicity [8], and β-amyloid toxicity [25]. However, other researchers reported that under serum starvation or inhibition of phosphatidylinositol 3-kinase activity, Chinese hamster ovary (CHO) cells synchronized by mitotic shake-off undergo apoptosis after progressing into S phase, as determined by [ 3 H]thymidine incorporation, another measure of DNA synthesis [30,31]. These discrepancies reflect the differences in cell types, transformed cell lines such as CHO cell or terminally differentiated neurons.…”
Section: Discussionsupporting
confidence: 67%
“…This notion was consistent with the conclusions in other neuronal cell death models, including mild cerebral ischemia [5], glutamate toxicity [8], and β-amyloid toxicity [25]. However, other researchers reported that under serum starvation or inhibition of phosphatidylinositol 3-kinase activity, Chinese hamster ovary (CHO) cells synchronized by mitotic shake-off undergo apoptosis after progressing into S phase, as determined by [ 3 H]thymidine incorporation, another measure of DNA synthesis [30,31]. These discrepancies reflect the differences in cell types, transformed cell lines such as CHO cell or terminally differentiated neurons.…”
Section: Discussionsupporting
confidence: 67%
“…caspase activation) and 40 % of cells were apoptosed after 3 days [5], leading to the hypothesis that there is a checkpoint early in G1 where cells decide to continue G1 and proliferation or to go into apoptosis. The mechanism behind this checkpoint might involve PI 3-kinase, an important proliferative protein for cell cycle progression, since the inhibition of this protein resulted in early G1 cell cycle arrest and increased caspase activation [148]. The notion of an early G1 checkpoint is consistent with the findings presented before of early apoptosis in neuronal and oligodendrocyte development, and this point could represent the more physiological apoptosis checkpoint that is important in development and tissue homeostasis.…”
Section: Apoptosismentioning
confidence: 54%
“…Expression of wild-type PTEN in tumor cells containing endogenous mutant PTEN inhibits AKT activity, induces G1 cell cycle arrest, and causes apoptosis. Evidence is accumulating that inhibition of PI3K with PI3K inhibitors causes G1 growth arrest and apoptosis in different carcinoma cells and normal cells [32][33][34][35]. A recent study reported that X-radiation in combination with the PI3K inhibitor LY294002 potentiated radiation-induced human esophageal cancer cell-killing synergistically, indicating that selective inhibition of the PI3K survival signaling pathway enhanced radiosensitivity in these cells [36].…”
Section: Resultsmentioning
confidence: 99%